Emotional Intelligence And Its Influence On Work-Life Balance Among Mixed Working Professionals In Coimbatore - Joy, Amala; Rajini, P. (Journal of Neonatal Surgery, 2025)
This study investigates the influence of Emotional Intelligence (EI) on Work-Life Balance (WLB) among mixed working professionals in Coimbatore. Emotional intelligence is increasingly recognized as a critical skill that helps professionals manage emotional demands, improve interpersonal relationships, and strike a balance between work and personal life. A total sample of 211 respondents from diverse occupational sectors was surveyed. The study uses a descriptive and comparative research design to analyze EI’s six core dimensions—Self-Awareness, Self-Regulation, Motivation, Empathy, Social Skills, and Workplace Emotional Adaptability—across various professions. Findings reveal a positive correlation between high EI and improved work-life balance across all professional groups, with minor variations based on industry-specific challenges.